Profiling of Proteins and Post Translational Modifications of Channa striatus Dried Meat - Kwan, Soon H.; Baie, Saringat; Nazri Ismail, Mohd (Current Proteomics, 2016)
Channa striatus is a freshwater snakehead fish that is commonly found in Malaysia. Several publications have reported the wound healing effect is available within the fish, yet the responsible biomolecules is yet to be clarified. In the current study, we have performed a comprehensive proteomic profiling of C. striatus meat using high sensitivity liquid chromatography tandem mass spectrometry. PEAKS Studio 7 was used for the protein profiling. Fractions collected using Gelfree fractionation system were also analyzed in order to maximize the protein detection. 75 proteins were identified in the Gelfree fractions as compared to the whole samples which only detected 42 proteins. Proteins detected were categorized and several potential proteins were highlighted as the possible candidates for the wound healing effect, including the structural proteins, enzymes, calcium related proteins and collagen. Post translationals modifications (PTMs) search were also conducted to complement the protein list. Methylation, hydroxylation and acetylation were the major PTMs detected. The study has provided an insight into the proteins and PTMs available in the species and showed that there is a high bio medicinal value for the Channa striatus. It serves as a fundamental for any future research to explore the wound healing property within the snakehead fish.
Keywords: fish